Gross Morphometrical Studies on the Kidneys of Male Guinea Pig (Cavia porcellus) - Seal, Tulumoni (Indian Journal of Veterinary Anatomy, 2020)
The gross morphometrical studies on the kidneys of male guinea pigs were conducted on four different age groups (0-2, 2-8, 8-16 and 16-32 weeks). Six guinea pigs were collected from each age groups and utilized for the study. The gross anatomical and morphometrical observations of both the kidneys were recorded in the guinea pigs of all the age groups. The kidneys were found to be retroperitoneal, reddish brown and bean shaped. They were located in the posterior part of the abdomen on each side of the vertebral column. The rightkidney was observed to be more cranial than the left. They were enclosed by a fibrous connective smooth capsule and fat surrounded the hilus and sides of each kidney. The longitudinal section of a kidney showed an outer dark cortex and an inner light medulla which appeared like an inverted pyramid. The kidney of guinea pig was found to be unipyramidal and non- lobulated. The gross morphometric parameters viz., weight, length, width, thickness, width of cortex and width of medulla of both the right and left kidneys were found to beincreased as age advanced.